Spatial and temporal variation of H and O isotopic compositions of the Xijiang River system, Southwest China. Issue 2 (4th March 2018) - Han, Guilin; Lv, Pin; Tang, Yang; Song, Zhaoliang
ABSTRACT: Ratios of stable isotopes of hydrogen and oxygen ( 2 H/ 1 H and 18 O/ 16 O) in river waters were measured to investigate the hydrological pathway of the Xijiang River, Southwest China. The δ 2 H and δ 18 O values of river waters exhibit significant spatial and temporal variations and the isotopic compositions vary with elevation, temperature and precipitation of the recharge area. Spatially, δ 18 O values of river waters from high mountain areas are lower than those from the lower reaches of the Xijiang River due to lower temperature and higher elevation for the recharge area. However, both 2 H and 18 O are enriched differently in river waters from the middle reaches during the high flow season, depending on the season and degree of anthropogenic disturbances (e.g. water impoundments). In contrast, deuterium excess ( d -excess) values of waters from the middle reaches are substantially lower than those from the upper and lower reaches, suggesting that river waters may be resided in the reservoir and evaporation increases in the middle reaches of the Xijiang River.